Comparative Stability of a Voltage-Source Inverter Using a Grid-Following/Grid-Forming Control Strategy for a PV Farm in a Hybrid Renewable-Energy System Fed to a Multimachine Power System Through an HVDC Link - Wang, Li; Liao, Zi-Hao; Li, Guan-Wei; Wang, Yaw-Juen (Conference record of the Industry Applications Conference, 2025)
This paper compares the power system stability of using grid-forming (GFM)- and grid-following (GFL)-based control strategies for the DC/AC voltage-source inverter (VSI) of a PV farm (PVF) in a hybrid renewable-energy system (HRES) connected to the IEEE 14-bus multimachine power system (MMPS) through a modular multilevel converter (MMC)-based high-voltage direct current (HVDC) link. The HRES consists of a doubly-fed induction generator (DFIG)-based offshore wind farm (OWF) and PVM with a solar module, a DC/DC boost converter, and a DC/AC VSI. The small-signal stability using root-loci plots under different operating conditions and transient responses subject to a large disturbance using GFL- and GFM-based control strategies for the studied VSI are compared. The simulation results show that the studied system using the GFM-based control strategy performs better than the GFL-based control scheme on the HRES in both small-signal stability and transient responses.